Pioneering the Establishment of Waste Banks as a Form of Community Empowerment - Novela Juliana; Paul Arjanto (CV. TOTUS TUUS, 2024)
The purpose of this community service activity is to socialize the making of garbage banks in increasing public awareness of the importance of not littering. In addition, the garbage bank is useful for all the people of Labuang village so that they do not throw garbage or burn rubbish, because the rubbish can generate money, crafts, etc., so that it can boost the economy of the people in Labuang village. The method of implementing the activity is carried out through socialization and assistance to the community of Kodangbang village, Namrole District, Buru Selatan Regency. The